Engineered tRNAs efficiently suppress CDKL5 premature termination codons - Stefano Pezzini; Aurora Mustaccia; Pierre Aboa; Giorgia Faustini; Alessio Branchini; Mirko Pinotti; Angelisa Frasca; Joseph J. Porter; John D. Lueck; Nicoletta Landsberger (Scientific Reports)
Abstract The CDKL5 deficiency disorder (CDD) is a severe neurodevelopmental disorder characterized by early-onset epilepsy, intellectual disability, motor and visual dysfunctions. The causative gene is CDKL5, which codes for a kinase required for brain development. There is no cure for CDD patients; treatments are symptomatic and focus mainly on seizure control. Several pathogenic variants are loss-of-function, but recent studies suggest that the CDD phenotype is sensitive to the CDKL5 gene dosage. Therefore, mRNA-targeted correction strategies that respect the physiological regulation of CDKL5 could be a valid alternative to augmentative gene therapy. Nonsense mutations cause ~ 11% of CDD cases, and these patients might benefit from readthrough therapies. We proved that drug-mediated readthrough efficiently suppresses premature CDKL5 nonsense codons, but the recoded kinase remained highly hypomorphic, curtailing the translational value of this pharmacological approach. In this study we explored if the recently developed Anticodon-edited tRNAs (ACE-tRNAs) offer an alternative readthrough strategy for CDD. Transfecting cells expressing different CDKL5 nonsense variants, we demonstrated that ACE-tRNAs efficiently restore full-length kinase synthesis. The recoded CDKL5 is correctly localized and catalytically active, thereby bringing tRNA-based therapy back into the spotlight for future investigations to assess the efficacy of this approach in correcting the pathological phenotype of CDD.